Effects of a Variable Dc-Port Voltage on the Half-Bridge-Based Modular Multilevel Converter for Drive Systems - Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2019)
The Modular Multilevel Converter (MMC) is a topology suitable for high-power medium-voltage variable-speed drives. However, the behaviour of this converter is highly affected by the power fluctuations of its modules. This paper analyses the influence of the dc-port voltage on these power fluctuations. It is demonstrated that the manipulation of this voltage offers several advantages for the operation of the drive. For example, it is possible to reduce: the voltage fluctuations in the capacitors, the capacitance of each cell or the application of mitigating variables during low machine speeds. Additionally, a reduction in the required common-mode voltage during low-speed operation is also feasible. The effectiveness of the proposed control schemes is demonstrated through simulation studies. © 2019 EPE Association.